2009
DOI: 10.1542/peds.2008-1930
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of CPR Quality During In-Hospital Resuscitation of Older Children and Adolescents

Abstract: This prospective, observational study demonstrates feasibility of monitoring in-hospital pediatric CPR. Even with bedside CPR retraining and corrective audiovisual feedback, CPR quality frequently did not meet AHA targets. Importantly, no flow fraction target of 10% was achieved. Future studies should investigate novel educational methods and targeted feedback technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 27 publications
3
94
0
Order By: Relevance
“…In human studies of CPR in out-of-hospital 81 and in-hospital settings, 78 -80 incomplete chest wall recoil was common, particularly when rescuers were fatigued. 78,81 Incomplete recoil during BLS CPR is associated with higher intrathoracic pressures and significantly decreased hemodynamics, including decreased coronary perfusion, cardiac index, myocardial blood flow, and cerebral perfusion. 76,82 Importantly, the incidence of incomplete chest wall recoil can be reduced during CPR by using electronic recording devices that provide real-time feedback.…”
Section: Technique: Chest Compressions (Box 4)mentioning
confidence: 99%
“…In human studies of CPR in out-of-hospital 81 and in-hospital settings, 78 -80 incomplete chest wall recoil was common, particularly when rescuers were fatigued. 78,81 Incomplete recoil during BLS CPR is associated with higher intrathoracic pressures and significantly decreased hemodynamics, including decreased coronary perfusion, cardiac index, myocardial blood flow, and cerebral perfusion. 76,82 Importantly, the incidence of incomplete chest wall recoil can be reduced during CPR by using electronic recording devices that provide real-time feedback.…”
Section: Technique: Chest Compressions (Box 4)mentioning
confidence: 99%
“…One LOE 4 out-of-hospital case series 83 documented a 46% incidence of incomplete chest recoil by professional rescuers using the CPR technique recommended in 2000, and 2 in-hospital pediatric case series demonstrated a 23% incidence of incomplete recoil that was more common just after switching providers of chest compressions (LOE 4 84,85 ). Another LOE 4 study 86 electronically recorded chest recoil during in-hospital pediatric cardiac arrests and found that leaning on the chest occurred in half of all chest compressions.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…31 Longer duration of CPR has also been associated with shallower chest compressions and excessive residual leaning force, which contribute to worse perfusion of heart and brain. 32 Nevertheless, prolonged duration of CPR was able to bridge many patients from pulselessness to return of spontaneous circulation and survival to discharge with a favorable neurological outcome. Although these data indicate that prolongation of CPR leads to worse outcomes, they also indicate that some children have a favorable neurological outcome even after prolonged CPR.…”
Section: Discussionmentioning
confidence: 99%